Determinants of Islamic Bank Employee Performance through Job Satisfaction - Mohammad Rizal; Arini Fitria Mustapita (Universitas Pembangunan Nasional Veteran Jakarta, 2023)
The Indonesian banking world is experiencing very rapid development, more and more new banks are popping up such as Islamic banks, so that business in the banking world is increasingly competitive. The research objective was to determine the effect of religious culture, and Islamic leadership on employee performance through job satisfaction. This research is causal associative research and examines the effect of intervening variables using path analysis. The research was conducted in 2022, from a saturated sample, a sample of 80 respondents was obtained. The results of this study are that religious culture and Islamic leadership partially have a significant effect on employee performance. Religious culture has no significant effect on job satisfaction. Islamic leadership has a significant effect on job satisfaction. Job satisfaction has a significant effect on employee performance. Religious culture has a significant influence on employee performance through job satisfaction. Islamic leadership has a significant influence on employee performance through job satisfaction. In the Sobel test, job satisfaction cannot mediate the relationship between religious culture and employee performance. Job satisfaction can mediate the relationship between Islamic leadership and employee performance. The implications of this research are that employees at Bank Syariah Indonesia feel high job satisfaction and have an understanding that working well for a living is worship. Leaders need to improve employee performance by implementing a culture of religiosity and increasing solidarity among employees to achieve optimal job satisfaction.